HIV-1 superinfection in a patient with known HIV-2 – A case report. (March 2020) - Ring, Kyle; Muir, David; Mackie, Nicola; Bailey, Angela C
We report a case of HIV-1 superinfection in a patient with established HIV-2 infection. The patient was not taking antiretroviral therapy, in line with criteria in national guidelines, and reported no risk for infection with HIV-1. This case serves as a reminder that patients infected with HIV-2 remain susceptible to HIV-1 infection. The protective effect of antiretroviral treatment against HIV-1 infection should be a consideration in treatment decisions for individuals with HIV-2 infection.